An Archaeology of Images. Investigation Into the Imaginative World of Robert Venturi - Francesca Sisci (img journal, 2023)
The research presented aims to investigate the theoretical work of the American architect, Robert Venturi, starting with the question: what was his dreamlike, imaginative, and creative world composed of? What role did the images that populated it play out and how were they transformed? From European explorations, through the book Complexity and Contradiction in Architecture, to the realization of Mother’s House, the study seeks to shed light on the evolution of theoretical thought through the observation from the images that Robert Venturi selected for himself, and which thus constitute themselves an archive of the visual and spatial research he conducted. It is thus from the images collected or taken that an attempt has been made to reconstruct the connection between visual perception, image, and theory.